Synthesis of Materials Based on La2O3 and SiO2 as Growth Stimulants for Salvia miltiorrhiza Bunge - Nguyen Vu Ngoc Mai; Nguyen Thi Ly Na; Tran Thi Thu Phuong; Do Minh The; Nguyen Thi Thanh Binh; Vo Manh Tien; Nguyen Tri Quoc; Nguyen Thi Phuong Le Chi; Mai Hung Thanh Tung; Cao Van Hoang (My University, 2023)
Synthesis of Materials Based on La2O3 and SiO2 as Growth Stimulants for Salvia miltiorrhiza Bunge
Keywords: La2O3/SiO2